Using an accelerated vehicle retirement program (AVRP) to support a mode shift: Car purchase and modal intentions following program participation - Lachapelle, Ugo (Journal of Transport and Land Use, 2015)
To stimulate the economy and reduce greenhouse gas emissions from older vehicles, most accelerated vehicle retirement programs (AVRPs) provide participants with incentives to purchase a new, less-polluting vehicle. The province of Québec also designed its AVRP as a mode-shift tool by providing alternative travel incentives to participants. Alternatives include public transit passes, rebates on bicycles and car-sharing memberships. In the absence of post-program assessment, the theory of planned behavior is used to assess participants’ modal intentions and intentions to purchase a new or used vehicle following par-ticipation. A subset (22 percent) of program participants (2009-2011; n=9070) filled out an optional survey about vehicle purchases and travel intentions. Age, gender, income, distance traveled in the previous year and perceived access to public transit were used as independent variables in logit and multinomial logit regressions. Car purchase intentions and traveling by car were associated with greater distance traveled. Higher-income participants were more likely to purchase new vehicles, and lower-income people and students were more likely to purchase used vehicles or refrain from any purchase. Alternative travel intentions were each associated with different socio-demographic characteristics. Québec’s program offers a promising incentive-based opportunity to influence mode shift if favora-ble circumstances are in place to enhance access to alternative travel modes.